Endonasal endoscopic surgery of skull base tumors an interdisciplinary approach - Draf, Wolfgang 1940-2011; Carrau, Ricardo L.; Bockmühl, Ulrike; Kassam, Amin B.; Vajkoczy, Peter (Thieme, 2015)
This book presents a complete step-by-step guide to endonasal endoscopic skull base surgery, written by prominent interdisciplinary specialists and reflecting important recent developments in the field. Combining the fundamentals of skull base anatomy and pathology with current diagnostic and interventional imaging techniques, Endonasal Endoscopic Surgery of Skull Base Tumors provides a solid clinical foundation for anyone working in this challenging and evolving specialty